Mental State Talk: Assessment through Wordless Picture Story Book Reading - Hafsa Khalil Toor, Rubina Hanif, (PJE, 2023)
Mental state talk involves words that describe the mental world of individuals. These could be words that are about thoughts, feelings, desires, intentions, and emotions. There has been dearth of research in Pakistan assessing the parents and teachers’ use of mental state talk in conversation with young children, commonly because of lack of assessment tool that are employed to measure the mental state talk in Pakistan. The present study aimed at validation and development of indigenous tool for the assessment of mental state talk of parents/teachers to use with children.